2017
DOI: 10.1371/journal.pone.0176992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen protects against oxidative stress-induced SH-SY5Y neuroblastoma cell death through the process of mitohormesis

Abstract: Inhalation of molecular hydrogen (H2) gas ameliorates oxidative stress-induced acute injuries in the brain. Consumption of water nearly saturated with H2 also prevents chronic neurodegenerative diseases including Parkinson’s disease in animal and clinical studies. However, the molecular mechanisms underlying the remarkable effect of a small amount of H2 remain unclear. Here, we investigated the effect of H2 on mitochondria in cultured human neuroblastoma SH-SY5Y cells. H2 increased the mitochondrial membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 33 publications
1
75
0
3
Order By: Relevance
“…In the context of the current lactate results, it is unclear whether HRW reduced anaerobic ATP production (reflected by lowered lactate) and/or improved mitochondrial aerobic-related lactate oxidation [34]. However, a recent in vitro H 2 study [35] reported an increased mitochondrial membrane potential, the enhancement of mitochondrial activity and ATP production, indicating that H 2 treatment activates OXOPHOS probably via an excessive calcium signalling pathway [36]. Therefore, it is tenable that in the current study, HRW may have had a stimulating effect on mitochondrial respiration or mitochondrial function performance resulting in either enhanced aerobic ATP production or lactate oxidation.…”
Section: Discussionmentioning
confidence: 88%
“…In the context of the current lactate results, it is unclear whether HRW reduced anaerobic ATP production (reflected by lowered lactate) and/or improved mitochondrial aerobic-related lactate oxidation [34]. However, a recent in vitro H 2 study [35] reported an increased mitochondrial membrane potential, the enhancement of mitochondrial activity and ATP production, indicating that H 2 treatment activates OXOPHOS probably via an excessive calcium signalling pathway [36]. Therefore, it is tenable that in the current study, HRW may have had a stimulating effect on mitochondrial respiration or mitochondrial function performance resulting in either enhanced aerobic ATP production or lactate oxidation.…”
Section: Discussionmentioning
confidence: 88%
“…One possible mechanistic explanation for the suppressive effect of HW on cellular senescence is that the lowering of ROS by HW downregulates DDR pathways. We demonstrated previously that H 2 induces a nuclear factor erythroid 2-related factor 2 (Nrf2)-dependent antioxidant response in cultured cells 33 and in a mouse model of sepsis 16 . A direct interaction between Nrf2 and p21 upregulates the antioxidant response 34 , which may downregulate further activation of DDR pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, some of the benefits of H 2 in plants are also mediated by increases in ROS production (Xie et al 2014). Furthermore, pretreatment of SH-SY5Y cells with H 2 protected them from subsequent oxidative stress induced by H 2 O 2 (Murakami et al 2017). In this case, H 2 acted as a mitohormetic effector by transiently increasing mitochondrial superoxide production, followed by an upregulation of Nrf2 transcription D r a f t and induction of other cytoprotective phase II proteins (Murakami et al 2017;Kura et al 2018).…”
Section: )mentioning
confidence: 98%
“…Additionally, in some cases molecular hydrogen also increases oxidant production (e.g. superoxide) (Murakami et al 2017), and so potentially provides hormetic benefits similar to those due to exercise. Lastly, hydrogen also increases Sirt3 expression (Wang D r a f t et al 2015), maintains mitochondrial membrane potential (Cui et al 2014), increases ATP production (Dohi et al 2014), and other benefits as shown in Table 1, all of which can provide an ergogenic and cytoprotective benefit for elite and non-elite athletes.…”
Section: Summary Of Hydrogen's Potential Benefitsmentioning
confidence: 99%